A new exceptionally preserved specimen of Dracaenosaurus (Squamata, Lacertidae) from the Oligocene of France as revealed by micro-computed tomography. Issue 6 (2nd November 2017) - Čerňanský, Andrej; Bolet, Arnau; Müller, Johannes; Rage, Jean-Claude; Augé, Marc; Herrel, Anthony
ABSTRACT: The best-preserved material of Dracaenosaurus croizeti, an almost complete and previously unpublished skull with a few associated postcranial bones (stylopodium, zeugopodium, and cervical vertebra), is described. The material comes from the locality of Cournon, a late Oligocene site in south-central France. Micro-computed tomography applied to this specimen revealed previously unknown internal osteological characters. Among lacertids, this taxon represents a notable phenomenon: it is an extreme durophagous specialist. Many of the newly observed cranial character states reflect the lifestyle of this lizard, because animals with a hard-shelled diet display a specialized cranial morphology associated with more massive cranial muscles. One unique character for Lacertidae is observed: the parietal-supraoccipital contact is formed by a ventrally deep parietal crest that fits into a bifurcate ascending process of the supraoccipital. In fact, such a connection represents the opposite to the connection in modern members of Lacertidae. Phylogenetic analysis recovered Dracaenosaurus inside Gallotiinae, a clade that would consist of the mainly Oligocene genera Pseudeumeces and Dracaenosaurus, the Miocene genus Janosikia, and the extant Psammodromus and Gallotia . Our study supports previous phylogenetic results and provides an example of the achievement of large size in mainland members of the stem of Gallotia, previously exemplified by Janosikia and Pseudeumeces . The extreme amblyodonty of Dracaenosaurus also confirms the view that herbivory in Gallotia is derived and may be the result of insularity. SUPPLEMENTAL DATA—Supplemental materials are available for this article for free atwww.tandfonline.com/UJVP Citation for this article: Čerňanský, A., A. Bolet, J. Müller, J.-C. Rage, M. Augé, and A. Herrel. 2017. A new exceptionally preserved specimen of Dracaenosaurus (Squamata, Lacertidae) from the Oligocene of France as revealed by micro-computed tomography. Journal of Vertebrate Paleontology. DOI: 10.1080/02724634.2017.1384738.